The Economics of Post Conflict Aid - McHugh, James (IMF Working Papers; Working Paper, 2002)
Post conflict aid is different from conventional development aid and has different effects on the recipient economy. The paper builds a theoretical model tailored around the main stylized facts of post conflict aid and traces the impact of different kinds of post-conflict aid on capital accumulation, growth, welfare, and resource allocation. While both humanitarian and reconstruction aid are welfare-enhancing, humanitarian aid reduces long-run capital accumulation and growth. Reconstruction aid, on the other hand, may increase the long-run capital stock and, if carefully designed, avoid the pitfalls of the Dutch disease.